2018
DOI: 10.1002/lary.27488
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional hypoglossal nerve stimulator after electrical cardioversion: A case series

Abstract: Objectives/Hypothesis Upper airway stimulation has demonstrated marked improvements in apnea‐hypopnea index, oxygen desaturation index, and quality‐of‐life measures in patients with moderate to severe obstructive sleep apnea (OSA) who cannot tolerate continuous positive airway pressure. Cardiac arrhythmias are common in patients with OSA and can require electrical cardioversion. We describe the first four reported cases of hypoglossal nerve stimulator (HGNS) dysfunction after electrical cardioversion and illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Symptoms resolved in 5 patients (71%) after minor interventions or adjustments to the HGNS device. Two patients (29%) did not overcome these adverse events; 1 developed an abscess that ultimately resulted in the explantation of the device, while the other experienced decreased tolerance of HGNS therapy following cardioversion, leading to disrupted sleep and discontinuation of HGNS in favor of PAP therapy …”
Section: Resultsmentioning
confidence: 99%
“…Symptoms resolved in 5 patients (71%) after minor interventions or adjustments to the HGNS device. Two patients (29%) did not overcome these adverse events; 1 developed an abscess that ultimately resulted in the explantation of the device, while the other experienced decreased tolerance of HGNS therapy following cardioversion, leading to disrupted sleep and discontinuation of HGNS in favor of PAP therapy …”
Section: Resultsmentioning
confidence: 99%
“…Failure of an HNS following ECV is a rare occurrence. A previous retrospective review of 201 patients by Vasconcellos et al ( 5 ) reported 4 instances of total device failure following repeated cardioversions for AF or direct cardioversion over the device. The devices in this series represented an older HNS technology that did not have electrical shielding and required surgical device replacement if damaged during ECV ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…More serious complications such as device exposure, pneumothorax, wound infection requiring explantation, hematoma requiring evacuation, and device malfunction after cardiac cardioversion have all be described, but are rare in frequency [29,30]. In general, when compared to alternative surgical therapies for the treatment of CPAP-resistant OSA, such as soft tissue surgery and orthognathic procedures, HGNS therapy complication rates are equally as low, if not lower, in these patients.…”
Section: Complicationsmentioning
confidence: 99%